2023
DOI: 10.1021/acsami.3c02647
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Imprinted Polymer Based on ZIF-8/DOX-HA for Synergistically Targeting Prostate Cancer Cells and Controlled Drug Release with Multiple Responses

Abstract: Improving the drug loading and delivery efficiency of biodegradable nanomaterials used for targeting prostate cancer (PCa) remains a challenging task. To accomplish this task, herein, a new surface molecularly imprinted polymer (ZIF-8/DOX-HA@MIP) was designed and constructed with a hyaluronic acid (HA)-modified zeolitic imidazolate framework-8 (ZIF-8) metal–organic framework loaded with doxorubicin (DOX) as a substrate and a responsive molecularly imprinted polymer film as a shell. Owing to the large surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…This decrease is attributed to the plentiful negatively charged carboxyl groups of HA, which have a coordinating effect with the Zn 2+ in the material, thus neutralizing some of the positive charges and leading to a decrease in potential. 29–31 All of the above results indicate the successful preliminary synthesis of the nanomaterials.…”
Section: Resultsmentioning
confidence: 66%
“…This decrease is attributed to the plentiful negatively charged carboxyl groups of HA, which have a coordinating effect with the Zn 2+ in the material, thus neutralizing some of the positive charges and leading to a decrease in potential. 29–31 All of the above results indicate the successful preliminary synthesis of the nanomaterials.…”
Section: Resultsmentioning
confidence: 66%
“…The peaks at 870 and 805 cm –1 have corresponded to another two N–H characteristic DOX peaks. Those results indicated the successful preparation of DZZ NPs with core–shell structure, large surface areas, and improved drug loading capacity. …”
Section: Results and Discussionmentioning
confidence: 91%
“…The cells incubated with HR-PDD NPs exhibited stronger DOX fluorescence than that of PDD NPs at 2 and 6 h. Fluorescence quantitative analysis using ImageJ software showed that the DOX fluorescence in the cells treated with HR-PDD NPs was 1.28 times higher as compared to that in the cells treated with PDD NPs at 6 h (Figure B). The significantly enhanced DOX fluorescence mainly benefited from the interaction between HA and the CD44 receptor. , HA bound the CD44 receptor overexpressed on tumor cells and facilitated the cell uptake of HR-PDD NPs. Next, we further examined the cellular internalization and subsequent DOX release profiles using flow cytometry (Figure C).…”
Section: Resultsmentioning
confidence: 98%